Tingkat Kepadatan Aktivitas Fisik dengan Denyut Jantung Istirahat - Paulus Parholong Siahaan; Bambang Purwanto; Raden Mohammad Budiarto; Irfiansyah Irwadi (Jurnal Ilmiah Kesehatan (JIKA), 2021)
Human life quality is related to the density of daily physical activity. Human diseases are related to how many steps to take within a day. The level of human physical activity can be measured using the IPAQ scoring protocol, created by WHO in 1988. The relationship between IPAQ score and health problems show to be correlated. Nevertheless, the relationship between the level of physical activity using the IPAQ score instrument and resting heart rate is not known yet. This researcher conducted this study to determine the relationship between physical activity level using the IPAQ scoring protocol and rest heart rate. This study is an observative analytic with a cross-sectional study design using a simple random sampling technique. This study was conducted in Surabaya from November 2019 until March 2020 using primary data in the form of the IPAQ scoring method and resting heart rate examination using the Polar Heart Rate tool, which is then processed using IBM SPSS Statistics 22. The IPAQ score and resting heart rate measurement results using polar heart rate tools showed that the most college student has a high degree of physical activity level (72%) and a normal level of resting heart rate (90%). When measured with the Pearson correlation test, the correlation of those two components has a negative and weak correlation (r= -0,337, p<0,05). Overall, the correlation of physical activity level and resting heart rate are inverted and weak. For further research can be done to assess other things like one’s external stressors and lifestyle.